Thermodynamics Affecting Glacier‐Released 4‐Nonylphenol Deposition in Alaska, USA. (17th May 2022) - Lyons, Rebecca; Weatherly, Shaun; Waters, Jason; Bentley, Jim
Abstract : The chemical and physical properties governing movement of 4‐nonylphenol through environmental compartments. Abstract: Glaciers have recently been recognized as a secondary source of organic pollutants. As glacier melt rates increase, downstream ecosystems are at increasing risk of exposure to these pollutants. Nonylphenols (NPs) are well‐documented anthropogenic persistent pollutants whose environmental prevalence and ecotoxicity make them of immediate concern to the health of humans and wildlife populations. As glacier melt increases, transport of NPs to downstream environments will also increase. Snow, ice, meltwater, and till for five glaciers in the Chugach National Forest and Kenai Fjords National Park, Alaska, USA, were investigated for the presence of 4‐nonylphenol (4NP). Average concentrations for snow, ice, meltwater, and glacial till were 0.77 ± .017 µg/L snow water, 0.75 ± .006 µg/L, 0.26 ± .053 µg/L, and 0.016 ± .004 µg/g, respectively. All samples showed the presence of 4NP. Deposition of 4NP downstream from glaciers will depend more on the ionic strength of the water than organic carbon to drive partitioning and deposition. Laboratory studies of partition coefficients showed that ionic strength contributed 59% of the driving force behind partitioning, while organic carbon contributed 36%. Evidence was found for interaction between organic carbon and the aqueous phase. The 4NP Setschenow constants ( K s ) were determined for particle types with varying percentages of organic carbon. Values of K s increased with the percentage of organic carbon. These relationships will shape further studies of 4NP deposition into the environment downstream of glacier outflow. Environ Toxicol Chem 2022;41:1623–1636. © The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.